How common is concurrent neurological and mood/anxiety disorder comorbidity over time? A population‐based cohort study in Ontario, Canada. (31st December 2021) - Maclagan, Laura C; Maxwell, Colleen J; Harris, Daniel A; Wang, Xuesong; Guan, Jun; Marrie, Ruth Ann; Hogan, David B; Austin, Peter C; Vigod, Simone N; Swartz, Richard H.; Bronskill, Susan E
Abstract: Background: Neurological disorders and mental health conditions, including mood/anxiety disorders, are a leading cause of disability and healthcare use. These disorders have shared risk factors and commonly co‐occur in older adults. Mood/anxiety disorders are often under‐diagnosed and under‐treated among those with neurological disorders, potentially leading to more rapid symptom progression, worse health outcomes and increased health care use. We estimated the relative and absolute rates of neurological and mood/anxiety disorder comorbidity among adults in Ontario, Canada. Method: We identified adults aged 40‐85 years on April 1 st, 2002 in Ontario, Canada using health administrative databases. These individuals were followed for up to 14 years until March 31 st, 2016. We estimated the association between between having a prior neurological disorder (dementia, Parkinson's disease (PD), and stroke) or mood/anxiety disorder and developing a different, incident neurological or mood/anxiety disorder using cause‐specific hazard models. Exposure to prior disorders was modeled as a time‐varying covariate and death was considered a competing risk. Individuals who were not at risk for the specific incident outcome disorder were excluded from that model. Result: All prior disorders were associated with increased rates of dementia: PD (adjHR= 4.05, 95%CI, 3.99‐4.11), stroke (adjHR=2.49, 95%CI, 2.47‐2.52), and mood/anxiety disorder (adjHR=1.79, 95%CI, 1.78‐1.80). Increased rates of PD were associated with prior dementia (adjHR=2.23, 95%CI, 2.17‐2.30) and mood/anxiety disorder (adjHR=1.77, 95% CI 1.74‐1.81), but not stroke (adjHR=1.04, 95% CI, 0.99 to 1.10). Rates of stroke were highest in persons with prior dementia (adjHR=1.56, 95% CI, 1.53 to 1.58) and showed more modest associations with PD (adjHR=1.21, 95% CI, 1.16 to 1.25) and mood/anxiety disorder (adjHR=1.09, 95% CI, 1.08 to 1.11). The associations were generally strongest in the six months following the prior disorder diagnosis, lowest in the interim periods (>six months to 10 years) and elevated in the later periods (10+ years) following diagnosis. Conclusion: We observed associations between pairs of prior and incident neurological disorders and mood/anxiety disorder among middle‐ and older‐aged adults. Neurological and mental health comorbidity is common. This should be considered in clinical practice guidelines for these conditions and may necessitate care across multiple providers.